The Fetomaternal Outcome of Pregnancy in Women with Thyroid Disease - Faryal Khan; Naina Khan; Zubaida Akhtar (Gandhara University, 2024)
OBJECTIVES To determine the frequency of fetomaternal outcomes in women with pregnancy with thyroid disease presented to Khyber Teaching Hospital Peshawar.  METHODOLOGY A descriptive observational study was conducted in Khyber's Obstetrics and Gynecology Department Teaching Hospital Peshawar from February to July 2022. A total of 160 pregnant patients with thyroid disease were included in the study. All patients were followed till delivery, and fetomaternal outcomes (gestational hypertension, pre-eclampsia, postpartum hemorrhage, mode of delivery, Oligohydramnios, birth weight, neonatal hyperbilirubinemia) were noted. RESULTS The age range in this study was from 18 to 40 years with a mean age of 29.787 +2.23 years, mean gestational age of 25.331+4.14 weeks, mean parity of 1.818+1.23 and mean weight of 68.462+3.30 kg. Hypothyroidism was seen in 76.9% of patients, and hyperthyroidism was seen in 23.1%. Gestational hypertension was observed in 11.9%, pre-eclampsia in 5%, postpartum haemorrhage in 47.5%, the cesarean section in 27.5%, Oligohydramnios in 11.3%, low birth weight in 21.3% and neonatal hyperbilirubinemia in 10.6%. CONCLUSION The most frequent complication observed in pregnancy with thyroid disease was postpartum haemorrhage, followed by cesarean section and low birth weight.